2020
DOI: 10.3390/healthcare8040494
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Older Adults’ Perceived Values of Using Smart Bracelets by Means–End Chain

Abstract: To cope with the demands for medical care in an aging society, smart healthcare wearable devices that can measure physiological signals are being regarded as the primary tools in medical care programs, allowing the users to acquire basic health data. Although the smart healthcare wearable devices could be applied to disease management and prevention that could help older adults control their health, older adults must be willing and able to use and continue to use them. In this research, interviews conducted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Therefore, app designers should include the function of ‘add to favourites’ in their app design to satisfy their users. Similar to the MEC‐related literature (e.g., Chakraborty & Sankaran, 2021; Jeng, Yeh, & Pai, 2020; Lin & Fu, 2018), the MEC's hierarchical value map resulting from this study provides users’ inner thoughts and preference information for marketers and designers to develop product and advertising strategies.…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, app designers should include the function of ‘add to favourites’ in their app design to satisfy their users. Similar to the MEC‐related literature (e.g., Chakraborty & Sankaran, 2021; Jeng, Yeh, & Pai, 2020; Lin & Fu, 2018), the MEC's hierarchical value map resulting from this study provides users’ inner thoughts and preference information for marketers and designers to develop product and advertising strategies.…”
Section: Resultsmentioning
confidence: 72%
“…As mentioned above, the PPG can be recorded on various areas of the body [ 67 ], so in certain situations where subject comfort is sought, and where noise due to movement is minimal, the PPG may be preferred over the ECG. Also, people tend to be more familiar with the idea of wearing a watch-like device [ 16 ], which could be a key factor in selecting which technology to use. On the other hand, the reuse of modules and code across manufacturers reduces the expense of product development [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when determining which technology to use to analyze cardiac activity, one has to consider the purpose of the recording, whether the analysis can be performed with ECG and/or PPG, as well as possible limitations, such as sensitivity to movement of the PPG [ 14 , 15 ], the use of electrodes for the ECG, and the comfort of the individual during data collection. On this last point, the PPG may be more comfortable with respect to the ECG, as it is found in a large number of commercial devices, such as smartwatches, with which subjects are more familiar [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Walking remains the most common form of casual exercise for such adults, and previous studies have shown that mild hikes have anti-aging effects and are a favorable form of casual exercise for less active older adults. Jeng et al [19] examined a large number of older adults and found that regular exercise greatly improved cerebral blood flow, cerebral vasodilation, and brain health.…”
Section: Life Satisfactionmentioning
confidence: 99%